Pulmonary Embolism after Arthroscopic Rotator Cuff Repair: A Case Report - Tadashi Yamamoto; Kazuya Tamai; Miwa Akutsu; Kazuo Tomizawa; Takuya Sukegawa; Yutaka Nohara (Case Reports in Orthopedics)
Total hip/knee arthroplasty may cause venous thromboembolism (VTE) as a postoperative complication. However, there are few reports on VTE after arthroscopic shoulder surgery. We report a patient who developed pulmonary embolism (PE) 6 days after arthroscopic rotator cuff repair but recovered without sequelae. In this case, the possibility of DVT of the lower limbs was denied by contrast-enhanced CT. Most possibly, the source of PE was deep vein thrombosis (DVT) of the upper limb under Desault fixation which showed arthroscopic surgery-related swelling postoperatively.